Shrinking wings for ultrasonic pitch production: hyperintense ultra-short-wavelength calls in a new genus of neotropical katydids (Orthoptera: Tettigoniidae). - Fabio A Sarria-S; Glenn K Morris; James F C Windmill; Joseph Jackson; Fernando Montealegre-Z (PLoS ONE, 2014)
This article reports the discovery of a new genus and three species of predaceous katydid (Insecta: Orthoptera) from Colombia and Ecuador in which males produce the highest frequency ultrasonic calling songs so far recorded from an arthropod. Male katydids sing by rubbing their wings together to attract distant females. Their song frequencies usually range from audio (5 kHz) to low ultrasonic (30 kHz). However, males of Supersonus spp. call females at 115 kHz, 125 kHz, and 150 kHz. Exceeding the human hearing range (50 Hz-20 kHz) by an order of magnitude, these insects also emit their ultrasound at unusually elevated sound pressure levels (SPL). In all three species these calls exceed 110 dB SPL rms re 20 µPa (at 15 cm). Males of Supersonus spp. have unusually reduced forewings (<0.5 mm(2)). Only the right wing radiates appreciable sound, the left bears the file and does not show a particular resonance. In contrast to most katydids, males of Supersonus spp. position and move their wings during sound production so that the concave aspect of the right wing, underlain by the insect dorsum, forms a contained cavity with sharp resonance. The observed high SPL at extreme carrier frequencies can be explained by wing anatomy, a resonant cavity with a membrane, and cuticle deformation.